Mandatory Research Biopsy Requirements Delay Initiation of Clinical Trials - Cheng, Jonathan H.; Tiulim, Justin W.; Zhou, Sheng; El-Khoueiry, Anthony; Nieva, Jorge (Frontiers in Oncology, 2019)
Background: There has been an increasing requirement for fresh tumor tissue to enroll in clinical trials in order to look for specific biomarkers. This has been shown to increase screening duration and increase screen failure rates. It was important to corroborate these results in other centers. Methods: This study is a non-randomized retrospective analysis of patients in one subset of patients seen by research nurses who operated in the standard head/neck and lung team not including patients in the phase 1 program. All patients were enrolled in clinical trials from January 16, 2013 to May 28, 2018 at USC Norris Comprehensive Cancer Institute in Los Angeles. Patients who were required to give fresh research biopsies prior to intervention were part of the research biopsy group. Results: In total, 76 patients were analyzed in this study. 33 patients were in the research biopsy group and 43 patients were in the no biopsy group. Trials that required a fresh biopsy had a longer median screening duration (30 vs 14 days) than trials that did not require a biopsy (p < .0001). Conclusions: Our study shows that requiring biopsies prior to clinical trial treatment results in a statistically significant delay in treatment. The informed consent forms that were part of clinical trials involving mandatory research biopsies did not reflect this delay in treatment. However, these delays did not result in a statistically significant decrease in number of days on trial or days until progression of disease.